The challenges of inclusive cross-scale collective action in watersheds - Swallow, B.M.; Johnson, Nancy L.; Meinzen-Dick, Ruth S.; Knox McCulloch, A (Informa UK Limited, 2006)
Increasing attention to watershed management is part of an international policy trend toward integrated water resource management. Integration is multidimensional across sectors, administrative regions, ministerial portfolios and levels of hydrologic structure and socioeconomic organization. Collective action is key. Individuals need to work effectively together to share common water points; upstream land users and downstream water consumers need to manage and resolve potential conflicts over water quantity and quality, while all the industries, farming communities, urban residents and public agencies that have interests in resource use and environmental quality need to agree on development and conservation objectives and approaches at the basin level. Initiatives that seek to foster collective action in watersheds need to account for the very different interests in water and watershed management. While there may be relatively straightforward ways to foster collective action at a local scale, some forms of collective action may, in fact, be detrimental to other stakeholders. In the developing world in particular, there are often geographic pockets and social groups that are chronically disadvantaged in collective and public processes. Water-users' associations and basin authorities may exacerbate these disparities and further marginalize already poor people. New statutory institutions may intentionally or inadvertently disempower effective customary local institutions. To enable project and program designers to address these challenges better, this paper lays out a framework for assessing the potential for, and implications of, individual and collective decisions in a watershed context. The framework integrates concepts drawn from the biophysical and social sciences, including new perspectives on watershed components, poverty, and collective action. Collective action is seen as a fractal process: collective action for water management at one level of social-spatial organization can have spillover effects at lower and higher levels of social-spatial resolution. To be pro-poor, watershed-management institutions must be genuinely inclusive, deliberately recognizing the interests, perspectives and knowledge of groups that may be systematically excluded from other political and social processes. Researchers, evaluators, watershed-management practitioners and others who apply the framework should be better placed to lay the foundations for that illusive goal: pro-poor, inclusive and resource-conserving development.